2014
DOI: 10.3109/03630269.2014.913517
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Iron Deficiency Anemia and Hemoglobinopathies Among College Students and Pregnant Women: A Multi Center Evaluation in India

Abstract: Although iron deficiency anemia is very common in India, systematic large studies on the prevalence and hematological consequences of iron deficiency among carriers of β-thalassemia (β-thal) and other hemoglobinopathies are lacking. A multi center project was undertaken to screen college/university students and pregnant women for iron deficiency anemia and various hemoglobinopathies. Fifty-six thousand, seven hundred and seventy-two subjects from six states, Maharashtra, Gujarat, Karnataka, West Bengal, Assam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…It is now clear that increased HbA 2 need not be an ‘invariable’ accompaniment of β‐thalassaemia trait. Thalassaemia trait patients who are iron deficient have slightly reduced but still elevated HbA 2 , although it remains possible that severe iron deficiency can at times reduce HbA 2 levels in β‐thalassaemia into a non‐diagnostic range (Verhovsek et al , ; Mohanty et al , ). Sometimes in β‐thalassaemia trait the HbA 2 is borderline or normal.…”
Section: Clinical Aspects Of Hba2mentioning
confidence: 99%
“…It is now clear that increased HbA 2 need not be an ‘invariable’ accompaniment of β‐thalassaemia trait. Thalassaemia trait patients who are iron deficient have slightly reduced but still elevated HbA 2 , although it remains possible that severe iron deficiency can at times reduce HbA 2 levels in β‐thalassaemia into a non‐diagnostic range (Verhovsek et al , ; Mohanty et al , ). Sometimes in β‐thalassaemia trait the HbA 2 is borderline or normal.…”
Section: Clinical Aspects Of Hba2mentioning
confidence: 99%
“…13 Anaemia is common in North-Eastern region of India. 14,15 The present study was done to evaluate the iron status in the CKD patients as iron deficiency is common in this region and this kind of study has not been done previously in this part of India.…”
mentioning
confidence: 99%
“…However several studies have shown that the HbA 2 levels in β-thalassaemia heterozygotes are not reduced so significantly to lead to a misdiagnosis of carriers of β-thalassaemia. 20,21 A β-thalassaemia mutation could not be identified in nine of the individuals with borderline/normal HbA 2 level; however five of them showed the presence of alpha gene triplication. Co-inheritance of a β-thalassaemia gene and α gene triplication can lead to a thalassaemia intermedia phenotype with a variable clinical presentation.…”
Section: Discussionmentioning
confidence: 89%
“…Associated iron deficiency anaemia can also lower HbA 2 levels, and iron deficiency is rampant in India. However several studies have shown that the HbA 2 levels in β ‐thalassaemia heterozygotes are not reduced so significantly to lead to a misdiagnosis of carriers of β ‐thalassaemia …”
Section: Discussionmentioning
confidence: 99%